Financial investigation and forensic accounting - Manning, George A. (CRC Press, 2011)
Economics of Crime Financial Crimes Offshore Activities Evidence Net Worth Theory Expenditure Theory Scenario Case RICO Net Worth Solution Tax Net Worth Solution RICO Expenditure Solution Tax Expenditure Solution Organized Crime Trial Preparation and Testimony Accounting and Audit Techniques Sources of Information Wagering and Gambling Fraud Prevention for Consumers Fraud Prevention for Business Money Laundering Interviewing Investigative Interview Analysis Banking and Finance Reports and Case Files Audit Programs Seizures and Forfeitures Judicial System Criminology Physical Security Search Wa.